2009
DOI: 10.1109/lmwc.2009.2013747
|View full text |Cite
|
Sign up to set email alerts
|

Study of Millimeter Wave Phase Shift in 40 GHz Hybrid Mode Locked Lasers

Abstract: Abstract-An investigation into using hybrid mode-locked lasers to implement millimeter wave phase shift is presented. The phase shift is measured directly using a vector network analyzer enabling straightforward characterization of such systems. Both magnitude and phase of the modulation response are measured and a "plateau" is observed in the magnitude response which corresponds to the locking range of the system. Phase shifts of greater than 90 are observed and such devices could have application in millimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…This condition is known as hybrid mode-locking. Such hybrid MLLs can also be used as mm-wave phase shifters under RF injection locking 0733-8724/$26.00 © 2010 IEEE [23], this shows their potential to be used in next generation smart antenna beam steering systems for WLANs. It has also been shown that in hybrid MLLs if the RF injected signal is itself modulated with baseband data, this data is imposed on the optical carrier such that it can be demodulated after a high speed PD.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is known as hybrid mode-locking. Such hybrid MLLs can also be used as mm-wave phase shifters under RF injection locking 0733-8724/$26.00 © 2010 IEEE [23], this shows their potential to be used in next generation smart antenna beam steering systems for WLANs. It has also been shown that in hybrid MLLs if the RF injected signal is itself modulated with baseband data, this data is imposed on the optical carrier such that it can be demodulated after a high speed PD.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows MLL injection locked measured S 21 amplitude and its phase and an overall phase shift of ~180 o is observed. It is important to note that the injection locked MLL presented in [6] and here is behaving like an electronic ILO by showing a phase shift of ~180 o for +0.6dBm injection power (P inj ) to the SA section shown in . But in reality it is an optoelectronic system which is fundamentally different and more complex then an electronic ILO system.…”
Section: Resultsmentioning
confidence: 86%
“…The MLL is supplied by HHI, Berlin [8] having a total device length of 1080μm which produces an output pulse repetition frequency of around 40GHz. The MLL has an excellent optical output power characteristic of ~ 7.5mW into a single mode fiber lens (SMF lens) at 110mA gain section current and at 15 o C. The MLL passive mode locking frequency range has been characterised and is found to be 446.7MHz as shown in [6]. A novel approach of hybrid injection locking the MLL has recently been presented using the vector network analyzer (VNA) [6] by exploiting the phase locking nature of a VNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations